CCAE: Centro de Ciências Agrárias e Engenharias - Ferreira Leal, Daniel; Andrade Garcia, Isabele; Vaz Andrade, Felipe; Ribeiro Passos , Renato; Pires Moraes, Alline; Evangelista, Camilla; Oliveira, Cristina; dos Santos Zucoloto, Rafael Antonio; Mechelli de Siqueira, Haloysio; Santana Tigre, Lucas Jordão; Mardgan, Leonardo; Ramos Alves, Fábio; et al. (Revista Guará, 2023)
Resumos de projetos do Centro de Ciências Agrárias e Engenharias